An ab-initio study of strongly correlated system FeSeCl7 (2025)
This study investigates the electronic and magnetic properties of the quantum halide FeSeCl7 using first-principles calculations. We performed density functional theory (DFT) calculations with both the Perdew-Burke-Ernzerhof (PBE) functional and the DFT+U method, incorporating a Hubbard U parameter determined via Cococcioni’s linear response approach to account for Fe d-electron correlations. Structural relaxation, equation of state, and density of states were analyzed for both functionals, providing insight into the material’s electronic and magnetic behavior.